Perceptions of dentists about care of HIV infected patients (Research, Society and Development, 2021)
Introduction: A cross-sectional observational study was performed involving 314 dentists in the city of Teresina, Piaui. Aims: The main objective of the present study was to evaluate the perception of dentists of Teresina, Piaui, in relation to the attitudes of HIV-infected patients. Material and methods: A cross-sectional survey was conducted among dentists of Teresina, Piaui. Positive perception was considered when the answer was “being able” and “not being afraid” to treat HIV-infected patients. Data were collected through a self-administered questionnaire that was statistically analysed using SPSS software version 20. Results: Most presented positive perception with regard to treating HIV-positive patients. Conclusion: Positive perception can be attributed to the continued education of these professionals.